2020
DOI: 10.3390/nu12123656
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hypoalbuminemia in Hospitalized Patients: A Clinical Matter or an Emerging Public Health Problem?

Abstract: Serum albumin levels are strongly associated with the morbidity, prognosis, and mortality rates of patients with hypoalbuminemia, which is a frequent problem during hospitalization. An observational retrospective study was carried out to analyze changes in albumin levels in hospitalized patients at the “Fondazione Policlinico Tor Vergata—PTV” in 2018. The prevalence of preexisting hypoalbuminemia at the time of discharge from hospital was investigated using a sample of 9428 patients. Information was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Clinical roles of albumin are frequently discussed in hospitalized patients [ 33 35 ]. However, there are few reports on the association between lower albumin levels and related factors in a general population.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical roles of albumin are frequently discussed in hospitalized patients [ 33 35 ]. However, there are few reports on the association between lower albumin levels and related factors in a general population.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is a valuable marker of in-hospital malnutrition and frailty. [16] An inadequate nutritional status, indicated by low albumin levels, can lead to poor inflammatory and immune responses to surgery. Hypoalbuminemia has been demonstrated to be associated with postoperative mortality in cardiac and non-cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the improvement of anemia, the upregulation of Alb and Ttr also indicated that RSGB improved the nutritional status of the thyrotoxicosis mice. Hypoalbuminemia is a common problem during hospitalization ( 41 ). Preoperative Ttr plays an important role in predicting postoperative complications ( 42 ).…”
Section: Discussionmentioning
confidence: 99%